Synthesis of Er1-xAxBa2Cu3O7-δ (A=Ca, Zn, Pb and Nd) superconductor ceramics via coprecipitation and their electrochemical characteristics - Al Aghbari, Elyas Sadeq Sulaiman (2012)
ErBa2Cu3O7-δ is a type II high temperature superconductor, which is known as the 123-system. This type of superconductor is classified as the most stable high temperature superconductor. This dissertation presents the doping effect of diamagnetic elements (Zn and Pb) and paramagnetic elements (Ca and Nd) in the Er-123 System using the coprecipitation method as a procedure of synthesis. Electrochemical studies of free and doped samples have been done to emphasize the doping effect on the copper electrochemical behaviour in the superconductor.